High aspect ratio, self-ordered iron oxide nanopores formed by anodization of Fe in ethylene glycol/NH4F electrolytes - Albu, Sergiu; Ghicov, Andrei; Schmuki, Patrik (Physica Status Solidi-Rapid Research Letters, 2009)
In the present work we show that highly self-ordered iron oxide nanopores can be anodically grown to high aspect ratios, in optimized fluoride-containing ethylene glycol electrolytes. The as-formed layers are amorphous and contain a significant amount of fluorides. By annealing the layers can be crystallized and the fluorides can be removed. At elevated electrolyte temperatures the nanoporous system shows a transition to a nanotubular structure.
EAM Import::2019-03-13